2015
DOI: 10.1111/1756-185x.12750
|View full text |Cite
|
Sign up to set email alerts
|

Atypical central retinal artery occlusion: an uncommon cause of retinopathy and visual loss in dermatomyositis

Abstract: Several ophthalmic manifestations in patients with dermatomyositis have been described but involvement of the retina is rare. A 39-year-old man diagnosed with dermatomysitis had developed sudden painless visual loss in the left eye. He was non-diabetic and non-hypertensive. He was on treatment with systemic prednisolone (50 mg/day) and methotrexate (7.5 mg/day) for dermatomyositis. His visual acuity was finger counting at 2 feet in the left eye and 6/6 in the right eye. Left fundus showed slight blurring of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…Multisystem vasculopathy in DM comprises myocardial infarction, ischaemic stroke , renal infarction , retinopathy , digital infarcts and microinfarcts in the muscles , indicating the involvement of vessels larger than capillaries. The significantly higher frequency of microinfarcts in edematous (80%) than in non‐edematous (34%) adult DM suggests a prominent role of ischaemia and vasculopathy in the underlying edema .…”
Section: Introductionmentioning
confidence: 99%
“…Multisystem vasculopathy in DM comprises myocardial infarction, ischaemic stroke , renal infarction , retinopathy , digital infarcts and microinfarcts in the muscles , indicating the involvement of vessels larger than capillaries. The significantly higher frequency of microinfarcts in edematous (80%) than in non‐edematous (34%) adult DM suggests a prominent role of ischaemia and vasculopathy in the underlying edema .…”
Section: Introductionmentioning
confidence: 99%
“…DM has also been associated with other retinal pathology, such as central retinal artery occlusion [10], central retinal vein occlusion [11], and optic neuropathy [12]. In one report of 43 patients with polymyositis and DM, only six (14%) had retinopathy [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, through clinical research covering treatment of acute cerebral infarction, myocardial infarction and acute retinal central artery occlusion in China and other countries ( 24 ), it was verified that rt-PA intravenous thrombolysis could significantly improve blood supply to acute ischemic cerebral and cardiac tissues and narrow the range of infarction so that it could reduce the disability rate and death rate caused by acute cardiac and cerebral infarction. Findings showed that rt-PA intravenous thrombolysis could improve patients' visual acuity by at least 3 lines within 24 h since the attacks of symptoms, and effectively improve as well as store their intraocular perfusion and visual function ( 27 ). In the present study, 12 cases of CRAO patients having attacks within 24 h were treated by intravenous medicine administration with rt-PA (0.9 mg/kg, the highest dosage being 90 mg).…”
Section: Discussionmentioning
confidence: 99%